2021
DOI: 10.1007/s13202-021-01216-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tailored water chemistry aqueous ions on foam stability enhancement

Abstract: Generating strong and stable foam is necessary to achieve in-depth conformance control in the reservoir. Besides other parameters, the chemistry of injection water can significantly impact foam generation and stabilization. The tailored water chemistry was found to have good potential to improve foam stability. The objective of this study is to extensively evaluate the effect of different aqueous ions in the selected tailored water chemistry formulations on foam stabilization. Bulk and dynamic foam experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…8−10 Alyousef et al studied the influence of chemical components in water on the foamability and foam stability of surfactants under reservoir geological conditions. 11,12 Wang et al studied the effect of nanoparticles on the stability of CO 2 foams and provided insights for subsequent studies on the stability of CO 2 foams. 13,14 films after surfactant foaming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8−10 Alyousef et al studied the influence of chemical components in water on the foamability and foam stability of surfactants under reservoir geological conditions. 11,12 Wang et al studied the effect of nanoparticles on the stability of CO 2 foams and provided insights for subsequent studies on the stability of CO 2 foams. 13,14 films after surfactant foaming.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are the key technology of CO 2 foam fracturing fluid, and their stability in foams is the main factor for evaluating their performance. Cao et al studied the influence of the colloidal particle charge on the stability of surfactant foams. Alyousef et al studied the influence of chemical components in water on the foamability and foam stability of surfactants under reservoir geological conditions. , Wang et al studied the effect of nanoparticles on the stability of CO 2 foams and provided insights for subsequent studies on the stability of CO 2 foams. , Uhlig et al found that polyelectrolytes affected the formation and stability of foam films after surfactant foaming. Petkova et al studied the influence of pH and the surfactant headgroup on the stability of polymer–surfactant foams . Based on the multiplicity of foam stability, Karakashav et al developed a foam-generating system based on sodium dodecyl sulfate (SDS) and discussed its stability .…”
Section: Introductionmentioning
confidence: 99%